Modeling Heterogeneous Brain Dynamics of Depression and Melancholia Using Energy Landscape Analysis - Regonia, Paul Rossener; Takamura, Masahiro; Nakano, Takashi; Ichikawa, Naho; Fermin, Alan; Okada, Go; Okamoto, Yasumasa; Yamawaki, Shigeto; Ikeda, Kazushi; Yoshimoto, Junichiro (Frontiers in Psychiatry, 2021)
Our current understanding of melancholic depression is shaped by its position in the depression spectrum. The lack of consensus on how it should be treated - whether as a subtype of depression, or as a distinct disorder altogether - interferes with the recovery of suffering patients. In this study, we analyzed brain state energy landscape models of melancholic depression, in contrast to healthy and non-melancholic energy landscapes. Our analyses showed significant group differences on basin energy, basin frequency, and transition dynamics in several functional brain networks such as basal ganglia, dorsal default mode, and left executive control networks. Furthermore, we found evidences suggesting the connection between energy landscape characteristics (basin characteristics) and depressive symptom scores (BDI-II and SHAPS). These results indicate that melancholic depression is distinguishable from its non-melancholic counterpart, not only in terms of depression severity, but also in brain dynamics.